Building land unit database for supporting land use planning in Thai Binh Province by integrating ALES and GIS - Xuan, Nhu Thi; Bao Hoa, Dinh Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 24 No 3, 2008)
Abstract